Characterization and Validation of ceRNA-Mediated Pathway–Pathway Crosstalk Networks Across Eight Major Cardiovascular Diseases - Song, Chao; Zhang, Jian; Liu, Yongsheng; Hu, Yinling; Feng, Chenchen; Shi, Pilong; Zhang, Yuexin; Wang, Lixin; Xie, Yawen; Zhang, Meitian; Zhao, Xilong; Cao, Yonggang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Recently, pathway analysis has become an important method to reveal the underlying mechanisms of diseases. Pathways that involved in crosstalks can regulate each other and co-regulate downstream biological processes. Furthermore, some genes in pathways can function with other genes via the relationship of competing endogenous RNA (ceRNA) mechanism, which has also been demonstrated to play key roles in cellular biology. However, whether ceRNAs are involved in pathway crosstalks or not is unclear. Here, we constructed the landscape of ceRNA mediated pathway-pathway crosstalks of 8 major cardiovascular diseases (CVDs) from 2,800 samples. Some common features shared by numerous CVDs were uncovered. A fraction of pathway-pathway crosstalks were conserved in multiple CVDs and a core pathway-pathway crosstalk network was identified, suggesting the similarity of pathway-pathway crosstalks among CVDs. Experimental evidences also demonstrated that the pathway crosstalks was functioned in CVD. We split all hub pathways of each pathway-pathway crosstalk network into 3 categories: common hubs, differential hubs and specific hubs, which could highlight the common or specific biological mechanisms. Importantly, after comparison analysis of hub pathways of networks, 480 hub pathway induced common modules were identified to exert functions in CVDs broadly. Moreover, we performed a random walk algorithm on hub pathway induced sub-network and identified 23 potentially novel CVD-related pathways. In summary, our study revealed the potential molecular regulatory mechanisms of ceRNA crosstalks in pathway-pathway crosstalks levels and provided a novel routine to investigate pathway-pathway crosstalks in cardiology. All CVD pathway-pathway crosstalks were provided in http://www.licpathway.net/cepathway/index.html.